Racial and Ethnic Differences in Teenage Fathers’ Early Risk Factors and Socioeconomic Outcomes Later in Life - Assini-Meytin, Luciana C. (Child Youth Care Forum, 2018)
BACKGROUND: Understanding racial differences in teenage fathers’ early risk factors and later outcomes is critical to inform programs for teenage fathers as our knowledge base on this population remains limited. OBJECTIVE: The goal of this study was to assess how teen fathers’ characteristics, including family background, delinquency, living arrangements, socioeconomic resources, and arrests, vary over time by race and ethnicity. METHOD: We analyzed National Longitudinal Study of Adolescent to Adult Health data. The analytic sample consisted of self-identified African American, Latino, and White males who fathered a child before the age of 20 (n = 313). Data come from three time points: adolescence, transition to adulthood, and young adulthood. RESULTS: Latino teen fathers came from families with lower educational attainment and greater reliance on public assistance. No statistically significant differences by race and ethnicity were found in parental involvement, school connectedness, marijuana use, and delinquency during adolescence. By their early 20s, a lower proportion of African American teen fathers were married compared to White and Latino teen fathers. By young adulthood, adjusted regression analyses showed that African American teen fathers were more likely to be arrested and earned a lower mean income than White teen fathers. CONCLUSIONS: Findings suggest that African American teen fathers, while no more disadvantaged or delinquent than the other two groups in their adolescence, experience greater accumulation of disadvantages over the life course. Intervention programs must consider the broader social and institutional context that may contribute to the disproportionate disadvantage among African American teen fathers in their young adulthood.